Increased Cytokine Levels Assist in the Diagnosis of Respiratory Bacterial Infections or Concurrent Bacteremia in Patients With Non-Hodgkin’s Lymphoma - Zhang, Lihua; Zhang, Jinping; He, Haiping; Ling, Xiaosui; Li, Fan; Yang, Zefeng; Zhao, Jinlian; Li, Huiyuan; Yang, Tonghua; Zhao, Shixiang; Shi, Keqian; Guan, Xin; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Non-Hodgkin’s lymphoma (NHL) is a form of tumor that originates in the lymphoid tissues. Bacterial infections are very common in NHL patients. Because most of the patients do not experience apparent symptoms during the initial stage of infection, it is difficult to detect the underlying condition before it progresses to a more critical level. The activation of the cytokines is a hallmark of inflammation. Due to the advantages of short detection time and high sensitivity of cytokines, many studies have focused on relationship between cytokines and infection. However, few studies have been conducted on NHL patients with infection. Therefore, we reviewed the cytokine profiles of 229 newly diagnosed NHL patients and 40 healthy adults to predict respiratory bacterial infection and bacteremia. Our findings revealed that IL-6(41.67 vs 9.50 pg/mL), IL-8(15.55 vs 6.61 pg/mL), IL-10(8.02 vs 4.52 pg/mL),TNF-β(3.82 vs 2.96 pg/mL), IFN- γ(4.76 vs 2.96 pg/mL), body temperature(37.6 vs 36.5°C), CRP(20.80 vs 4.37 mg/L), and PCT(0.10 vs 0.04 ng/mL) levels were considerably greater in NHL cases with respiratory bacterial infections relative to NHL cases without infection (P<0.05). Furthermore, IL-6(145.00 vs 41.67 pg/mL), IL-8(34.60 vs 15.55 pg/mL),temperature(38.4 vs 37.6°C), PCT(0.79 vs 0.10 ng/mL), and CRP(93.70 vs 20.80 mg/L) levels in respiratory infectious NHL patients with more severe bacteremia were considerably elevated than in patients with respiratory bacterial infections only (P<0.05). Remarkably, increased levels of IL-6 and IL-8 are effective in determining whether or not pulmonary bacterial infectious NHL patients have bacteremia. Temperature, PCT, and CRP all have lower sensitivity and specificity than IL-6. IL-6 ≥18.79pg/mL indicates the presence of pulmonary bacterial infection in newly diagnosed NHL patients, and IL-6 ≥102.6pg/mL may suggest pulmonary bacterial infection with bacteremia. In short, this study shows that cytokines can be advantageous in the diagnosis and differentiation of pulmonary bacterial infection and bacteremia in newly diagnosed NHL patients and may also guide for the use of clinical antibiotics.